Spreminjanje rabe tal v severnih Goriških brdih - Petek, Franci (Geografski vestnik, 2007)
The low hills of Goriška brda have a distinctly dual appearance. In their southern part, agricultural or vineyard land use is very intensive for Slovene conditions, and the proportion of surface occupied by vineyards has remained almost the same since the first half of the 19th century. In contrast, northern part of Goriška brda has experienced intensive overgrowth. The proportion of forest today is more than 80% whereas during the period of the greatest extent of farmland it only covered 30%. The reason for this can be found primarily in changed social conditions.
Keywords: kulturna pokrajina; podeželje; rural area; kmetijska zemljišča; raba tal; spremembe; Goriška brda; Gorizia Hills; Slovenia; Slovenija